2016
DOI: 10.1515/jec-2016-0014
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Human Capital for National Innovation Capability in Eu Countries

Abstract: Abstract. Innovation is essential for economic growth in developed countries. One of the most important sources of innovation is human capital. In this article, state of human capital in EU countries is investigated in order to show the relationship between human capital and national innovation performance. In the first part, theoretical assumptions of human capital importance for innovation processes are analysed. Secondly, measures of human capital are analysed and a measurement model is presented. This mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 54 publications
0
9
0
3
Order By: Relevance
“…We obtained the results shown in table (2). The previous regression models show that there are clear and significant structural differences between national innovation systems in the BRICS countries.…”
Section: Fig 2 Overall Niss' Rank Of the Brics Countriesmentioning
confidence: 86%
See 1 more Smart Citation
“…We obtained the results shown in table (2). The previous regression models show that there are clear and significant structural differences between national innovation systems in the BRICS countries.…”
Section: Fig 2 Overall Niss' Rank Of the Brics Countriesmentioning
confidence: 86%
“…In addition to spending on education as a percentage of GDP. This is indicative of the Russian government's approach to building a strong human capital capable of acquiring the necessary technological skills in the future [20].Since the development of human capital is one of the most important factors promoting and supporting innovation [2].…”
Section: Innovation Dimensionmentioning
confidence: 99%
“…La base de la capacidad de absorción es la adquisición de nuevas habilidades a través de los trabajadores de la empresa en su formación y experiencia y las capacidades organizacionales logradas por la gestión del conocimiento [20]. Estas capacidades también pueden incrementarse mediante capacidades de formación y aprendizaje [21]. Por tanto, las habilidades y capacidades organizativas del capital humano de la empresa deben potenciarse mediante la formación para aumentar o modificar los conocimientos existentes.…”
Section: Do Not Removeunclassified
“…The second is to use the model to quantitatively analyze the influence and contribution of human capital. Rasa et al (2016) respectively measured the impact and contribution of human capital in different regions with the help of Granger causality test model, Zheng (2017) with the help of Getis spatial filtering model, Chen et al (2019) with the help of spatial Dubin model and Harris et al (2019) with the help of human capital behavior model, and all found that there is a continuous positive effect on industrial transformation and upgrading. The increase of labor cost can promote the enterprise to develop the productivity of the employees instead of reducing the employees, thus promoting the technological progress and industrial upgrading of the enterprise (Riley et al, 2017).…”
Section: Human Resource Development Under the Background Of High-quality Developmentmentioning
confidence: 99%